1999
DOI: 10.1172/jci6024
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular adhesion molecule-1 modulates β-chemokines and directly costimulates T cells in vivo

Abstract: Figure 7Expression of β-chemokines by stimulated effector T cells. Supernatants from effectors stimulated for CTL assay were collected at day 6 and tested for β-chemokine profile using ELISA kits for macrophage inflammatory protein-macrophage inflammatory protein-1α (MIP-1α) (a), macrophage inflammatory protein-1β (MIP-1β) (b), and regulated on activation normal T-cell expression and secreted (RANTES) (c).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 37 publications
1
29
0
Order By: Relevance
“…2), we cannot exclude the possibility that ICAM-1 expressed on fibroblasts has some direct role for cytokine production in infiltrated T cells in the lesional skin. It has been demonstrated that ICAM-1 can provide T cell costimulatory signals that are independent of CD86/CD28 pathway (48). Although CD4 ϩ T cells from TSK/ϩ mice showed Ͼ2-fold increase in surface expression of CD44, an activation marker of T cells (38), CD44 expression on CD4 ϩ T cells from wild-type mice increased to a similar level by coculturing with TSK/ϩ fibroblasts, but not with ICAM-1 Ϫ/Ϫ TSK/ϩ fibroblasts (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…2), we cannot exclude the possibility that ICAM-1 expressed on fibroblasts has some direct role for cytokine production in infiltrated T cells in the lesional skin. It has been demonstrated that ICAM-1 can provide T cell costimulatory signals that are independent of CD86/CD28 pathway (48). Although CD4 ϩ T cells from TSK/ϩ mice showed Ͼ2-fold increase in surface expression of CD44, an activation marker of T cells (38), CD44 expression on CD4 ϩ T cells from wild-type mice increased to a similar level by coculturing with TSK/ϩ fibroblasts, but not with ICAM-1 Ϫ/Ϫ TSK/ϩ fibroblasts (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, the in vivo responses to ICAM-1-mediated costimulation may be more complicated. Kim et al (32) have found that the in vivo expression of ICAM-1, with cDNA expression cassettes, causes enhancement of both immunogen-specific CD4…”
Section: Discussionmentioning
confidence: 99%
“…An apparent contrary result was also obtained in L. (L.) donovani model of visceral leishmaniasis where CD86 blocking increased IFN-γ production and reduced parasite burden (Murphy et al 1997). A possible explanation for these results is that a more complex picture could be involved in driving lymphocytes to TH1 or TH2 response (Kim et al 1999). Whereas CD80 or CD86 expression leads to high IL-4 and IL-10 production by naive CD4 T cells, co-expression of CD54 plus CD80 or CD 86 resulted in decreased IL-4 and IL-10 production (Luksch et al 1999).…”
Section: Parasite's General Strategy At the Initial Phases Of Leishmamentioning
confidence: 99%